Nativisation and acceptability in Malaysian English - Wahid, Ridwan (2013)
Malaysian English (ME) grammar is said to contain unique, local features that exist alongside exonormative counterparts. Such usages are often regarded as errors by prescriptivists although their widespread use especially through the basilect and mesolect may prompt some descriptivists to label them as innovations instead. Probably due to the lack of codification, the distinction between ‘error’ and ‘innovation’ with regard to nativised features is even less clear among speakers of ME themselves. This paper aims to prove that the blurring of this distinction characterises much of the ME that is used by some of its most dedicated speakers. It presents findings from a survey of acceptability of 11 deviant grammatical items adapted from Bautista (2004) and 28 divided usages adapted from Lee (2001). In contrast to previous studies that relied on speaker proficiency as an indicator of nativisation, this survey targets a group of two contrastive speakers: English majors and non-English majors. The two groups are differentiated based on the extent of their use of English at present and in the future; collectively English majors tend to use more English in their studies and future workplaces than non-English majors. Although use of a language and proficiency in that language may be interrelated, the former can be usefully isolated so that its effect on nativisation can be studied.